Britain and the Association Internationale du Congo, January 1884 - February 1885 - Paul Swanepoel (Modern Africa)
In 1884, Britain was concerned with negotiations surrounding three agreements that were closely related to the Berlin West Africa Conference, which began in November 1884 and ended in February 1885; the Anglo-Portuguese treaty signed on 26 February 1884, which sparked the diplomatic crisis that resulted in the conference; a pre-emption agreement, signed between the Association Internationale du Congo and France on 23 April 1884; and the recognition of the Association as a sovereign power by Britain after the conference had begun on 16 December 1884. During the period under examination, there was an emphasis on territorial negotiations regarding the lower Congo River between Britain, France, Germany, Portugal, and the Association Internationale du Congo. The present article focuses on the background to these agreements thereby providing an important contextual framework for what was discussed at the Berlin Conference.